Incentive Communication Management 30 Packages Towards Work Motivation Of Courier PT. Shopee Express Warehouse Metropolitan Trade Center - Fauzan Aziman Lisli; Anang Anas Azhar (IHSA Institute, 2022)
The purpose of this study is to see how the 30 package incentive communication management affects the work motivation of Shopee Express couriers at the Medan Metropolitan Trade Center (MMTC) warehouse. Communication management theory is used as a theoretical foundation for analyzing the problems in this qualitative research. The informants in this study were the MMTC warehouse's warehouse leader, operator, courier team leader, and two Shopee Express couriers. Interviews, observation, and documentation were used to collect data from all informants in this study, which used a phenomenological study approach in which researchers attempted to find meaning from the phenomena experienced by informants related to the 30 package incentive program. In this study, data analysis is descriptive, which summarizes all data collected from interviews into empirical and solid data that readers can easily understand. This study demonstrates that Shopee Express's 30-package incentive program at the MMTC warehouse is very effective in increasing employee motivation, particularly among warehouse couriers.